Boosting agricultural productivity through parcelization of collective certificate of land ownership awards - Ivory Myka R. Galang (Philippine Institute for Development Studies (PIDS), 2020)
Farmers awarded with lands under a collective CLOA (CCLOA) have been experiencing problems arising from the collective arrangement (e.g. boundary issues, disputes with other collective members). These issues discourage many farmers from making long-term investment decisions on their land, thereby resulting in lower productivity. With a strong directive from President Rodrigo Duterte, currently, the Department of Agrarian Reform is committed to ensure the swift implementation of the Parcelization program, which aims to subdivide collectively-owned CLOAs, whose farmers are not engaged in collective farming. This paper aims to identify benefits and problems in relation to the subdivision of collective land titles. Based on findings of existing studies, individual land ownership has a positive impact on farmers' decisionmaking and on his/her farming outcomes. Although limited in sample observations, the analytical exercise using Project ConVERGE's survey data provided additional evidence favoring the acceleration of the subdivision of CCLOAs. It was also pointed out that while parcelization is being pursued, other rural development strategies, such as farm consolidation, could also be undertaken. For a faster and smoother implementation of parcelization program, it would be helpful to adopt a modern cadaster and record-keeping system and to improve agrarian justice delivery system of DAR.
Keywords: 330; Certificate of Land Ownership Award; CLOA; collective CLOA; individual CLOA; ARBO; land reform; agricultural productivity; DAR